Reconstructing the Greek Summer: the role of the Press for restarting travel and tourism in the Covid-19 pandemic era - Petros Kosmas; Petros Giannoulis; Maria Panagopoulou; Leonidas Vatikiotis; Hristo Andreev; Antonis Theocharous (Via@)
The present research focused on exploring the role that the press plays in the recovery procedure of the tourism sector in times of pandemic crisis. Towards achieving this goal, selected sources of the Greek press were in-depth analysed to evaluate Greek Government’s management of the resumption of Greek tourism following the first wave of the COVID-19 pandemic in the summer of year 2020. Content Analysis was applied to the editorial columns of four Greek daily newspapers to examine whether and to what extent the political affiliation of these newspapers influenced their perception of the decision-making process and the management concerning the resumption of tourism by the Greek government. Τhe research further explores the ways these newspapers attempt to reshape government’s narrative towards the restarting of Greek tourism.